Stavbna pravica - sedem let po njeni uveljavitvi - Vlahek, Ana (Pravni letopis, 2010)
Superficies is a new property right in the Slovene law as of 2003 when the new Code of Property Law entered into force. Legal theory and business practice have opted for its introduction as it enables a very practical formation of a legal relationship on immovables owned by one person but offered to another for building his or her own edifice on it. Thus far, superficies has oftentimes been made use of in particular with regard to municipal land. As superficies is primarily established only by registration in the land register, the land registry was the first to be confronted with the new right's substance, beside the parties and their legal representatives. Although superficies has formed part of the property law corpus only for the last seven years, the courts, too, have already come across its application. Cases deal primarily with relationships that had arisen decades ago, but superficies is nevertheless perceived as a possible frameworkfor their regulation. How the courts are to apply and interpret the provisions on superficies, there by crystallizing its content, however, remains to be seen.
Keywords: lastninska pravica; stavbna pravica; stavbna zemljišča